Distribution, transmission and penetrance of hereditary juvenile glaucoma linked to manic-depressive psychosis and diabetes mellitus - Valtot, F. (Array, 1990)
Over 100 living cases of hereditary juvenile glaucoma have been discovered in one French family with a family tree documented back to the 15th century. Transmission of the glaucoma is autosomal dominant and is significantly linked to manic-depressive psychosis and diabetes mellitus. A molecular genetic study is underway using a polymorph probe technique distributed on the genome in an attempt to locate the responsible gene or genes